2020
DOI: 10.1080/13880209.2020.1730913
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of grape seed procyanidin on isoflurane-induced cognitive impairment in mice

Abstract: Context: Oxidative imbalance-induced cognitive impairment is among the most urgent clinical concerns. Isoflurane has been demonstrated to impair cognitive function via an increase in oxidative stress. GSP has strong antioxidant capacities, suggesting potential cognitive benefits. Objective: This study investigates whether GSP pre-treatment can alleviate isoflurane-induced cognitive dysfunction in mice. Materials and methods: C57BL/6J mice were pre-treated with either GSP 25-100 mg/kg/d for seven days or GSP 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Confounding multi-factorial causes of POCD and oxidative stress are important in the pathogenesis of POCD (Netto et al, 2018 ). Our research group used natural extracts, such as green tea polyphenols (Song et al, 2019 ) and grape seed procyanidin (Gong et al, 2020 ), to alleviate oxidative stress levels in the hippocampus, both of which reversed the cognitive dysfunction induced by long-term isoflurane anesthesia. How to alleviate the level of oxidative stress caused by surgery may be one of the strategies for the treatment of POCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confounding multi-factorial causes of POCD and oxidative stress are important in the pathogenesis of POCD (Netto et al, 2018 ). Our research group used natural extracts, such as green tea polyphenols (Song et al, 2019 ) and grape seed procyanidin (Gong et al, 2020 ), to alleviate oxidative stress levels in the hippocampus, both of which reversed the cognitive dysfunction induced by long-term isoflurane anesthesia. How to alleviate the level of oxidative stress caused by surgery may be one of the strategies for the treatment of POCD.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data suggested that surgery induced cognitive impairment, and the impairment could be attenuated by ISRIB. To elucidate the molecular mechanism underlying cognitive impairment, our previous studies showed that two cognitive-related proteins, P-NR2B and BDNF, are damaged in the hippocampus of POCD mice (Song et al, 2019 ; Gong et al, 2020 ). In the current experiments, we also detected these two proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, anthocyanins were not detected in methanolic extracts of P. patens separated by HPLC method (Wolf et al, 2010). Similarly, several SCMs like procyanidin and luteolin were detected in P. nutans, and functioned as an efficient antioxidant (Gong et al, 2020). Notably, several Antarctic mosses (e.g., Bryum pseudotriquetrum, C. perpureus, and Schistidium antarctici) and liverwort (M. polymorpha) possess anthocyanins, but Antarctic algae do not have anthocyanins (Singh et al, 2011).…”
Section: Flavonoid Metabolites Play An Important Role In Uv-b Toleran...mentioning
confidence: 99%
“…Notably, PCs and some of their metabolites stimulate CREB, acting as a molecular switch from short- to long-term memory, based on the interplay of the CREB-SIRT1 axis (Zhao et al, 2019 ). Grape seed PCs (GSPCs) improve isoflurane-induced cognitive dysfunction by protecting against perturbing antioxidant enzyme activities and the NR2B/CREB pathway (Gong et al, 2020 ). In addition, the PCs effectively inhibit the aggregation of human islet amyloid polypeptide (hIAPP) and Aβ through hydrophobic and hydrogen bonding interactions and also dissolve the aged fibrils (Xu et al, 2021 ).…”
Section: Polyphenolsmentioning
confidence: 99%